Service research and innovation : 5th and 6th Australasian Symposium, ASSRI 2015 and ASSRI 2017, Sydney, NSW, Australia, November 2-3, 2015, and October 19-20, 2017 : revised selected papers /: 5th and 6th Australasian Symposium, ASSRI 2015 and ASSRI 2017, Sydney, NSW, Australia, November 2-3, 2015, and October 19-20, 2017 : revised selected papers. ([2018]) - Unknown
No abstract available